STUDENTS’ READING BASED-MAIN IDEAS ON PASSAGES AT THE SECONDARY EDUCATION - Yogo Gandjarwati (Journal of English for Academic and Specific Purposes, 2020)
Reading comprehension is crucial skill for both English as a Second Language (ELS) and English as a Foreign Language (EFL) students. To develop the students’ reading  ability, the use of main idea of paragraphs in comprehending the passage  becomes an alternative solution to be used in teaching. This study is categorized as a Classroom Action Research (CAR). It was applied in use of main idea of paragraphs in comprehending the passage to improve the students’ reading skills. The population of the study is 36 students at the second year students of SMAN 1 Kauman. The instruments of the study consisted of reading test and questionnaries. Based on the research finding  that the students’ reading skill and their motivation were still low, as it was indicated in pre-study, the score result was under KKM or the average score is 65 ,55. Therefore, the researcher tried to apply  the use of reading based main ideas on coomprehending  passages to improve the reading skill. The writer found in the first cycle the average score is 77,00. The next cycle done by the writer repaired the strategy in teaching   reading through main idea of paragraphs. It was proved that the students’ score average is 80,22. They passed and got the better score than previous result.  It’s concluded that the use of main idea of paragraphs in comprehending the passage was able to improve the students’ reading skill. The students’ interest in reading comprehension through main idea of paragraphs is also good. It has shown  the result of questionnaire (83,33%).